A Single Item Measure of Self-Control – Validation and Location in a Nomological Network of Self-Control, Boredom, and If-Then Planning - Wolff, Wanja; Bieleke, Maik; Englert, Chris; Bertrams, Alex; Schüler, Julia; Martarelli, Corinna S. (Social Psychological Bulletin, 2022)
Self-control is a highly adaptive human capacity and research on self-control is booming. To further facilitate self-control research, especially in conditions where time-constraints might render the use of multi-item measures of self-control problematic, a validated time-efficient single item measure would be an asset. However, such a measure has not yet been developed and tested. Here, we address this gap by reporting the psychometric properties of a single item measure of self-control and by assessing its localization within a larger theorized psychometric network consisting of self-control, boredom and if-then planning. In a high-powered (N = 1553) study with paid online workers from the US (gender: 47.3% female, 51.7% male, 1% other; age: 40.36 ± 12.65 years), we found evidence for the convergent validity (Brief Self-Control Scale), divergent validity (Short Boredom Proneness Scale and If-Then Planning Scale), and criterion validity (objective and subjective socio-economic status) of the single item measure of self-control (“How much self-control do you have?”). Network psychometrics further revealed that the single item was part of the self-control subnetwork and clearly distinguishable from boredom and if-then planning, which together with self-control form a larger psychometric network of psychological dispositions that are relevant for orienting goal directed behavior. Thus, the present findings indicate that self-control can be adequately captured with the single item measure presented here, thereby extending the methodological toolbox of self-control researchers by a highly-time efficient measure.